Geography or skills: what explains Fed Wachters' forecast accuracy of US monetary policy? - Helge Berger; Michael Ehrmann; Marcel Fratzscher (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2008)
The paper shows that there is a substantial degree of heterogeneity in the ability of Fed watchers to forecast US monetary policy decisions. Based on a novel database for 268 professional forecasters since 1999, the average forecast error of FOMC decisions varies 5 to 10 basis points between the best and worstperformers across the sample. This heterogeneity is found to be related to both the skills of analysts - such as their educational and employment backgrounds - and to geography. In particular, forecasters located in regions which experience more idiosyncratic economic conditions perform worse in anticipating monetary policy. This evidence is indicative that limited attention and heterogeneous priors are present even for anticipating important events such as monetary policy decisions. Moreover, the paper shows that such heterogeneity is economically important as it leads to greater financial market volatility after FOMC meetings. Finally, policy-makers are not impotent in influencing such heterogeneity as Fed communication is found to affect forecast accuracy significantly.
Keywords: E52; E58; G14; 330; Monetary policy; forecast; Federal Reserve; FOMC; geography; skills; heterogeneity; survey data; communication; United States.; Geldpolitik; Zentralbank; Wirtschaftswissenschaftler; Konjunkturprognose; Bewertung; USA